Enhanced surveillance of infectious syphilis in New Zealand sexual health clinics. (October 2013) - Psutka, Rebecca; Dickson, Nigel; Azariah, Sunita; Coughlan, Edward; Kennedy, Jane; Morgan, Jane; Perkins, Nicky
Following a rise in cases of infectious syphilis in New Zealand, national enhanced surveillance at sexual health clinics was initiated. All public sexual health clinics reported monthly on the number of cases seen, and completed a coded questionnaire on each case. Monthly reports to routine surveillance were compared and discrepancies reconciled. During 2011, 72 cases of infectious syphilis were reported. The majority (83%) were among men who have sex with men who were mainly infected in New Zealand and had an ethnic profile similar to all New Zealanders. Most heterosexual infections occurred overseas, among people of non-European non-Maori ethnicity. About half the cases had symptoms on presentation. Overall, 18% of men who have sex with men were HIV positive. Resurgent syphilis in New Zealand disproportionally affects men who have sex with men, amongst whom HIV is prevalent. Men who have sex with men should be aware of the risks and symptoms of syphilis and encouraged to have regular sexual health checks including serology testing. Control of syphilis should be included in the strategy to check HIV spread. Syphilis serology should continue to be part of routine immigration and antenatal screening, and where clinically indicated. Enhanced surveillance was easily initiated for an uncommon condition seen at sexual health clinics, and provided valuable information.